Development of an Interactive E-Module Based On Flipbook Protista Material To Improve Student Biology Learning Outcomes - Iwan*, Iwan; Sirait, Silvia Hanna Kusuma; Fahmi, Dian (Jurnal IPA & Pembelajaran IPA, 2024)
The development of a flipbook-based interactive e-module is an innovative step in increasing the effectiveness of biology learning, especially Protista material. Protista is a group of eukaryotic organisms that includes various microorganisms such as protozoa, unicellular algae, and others. This research aims to develop an interactive e-module based on flipbook material on protists that is valid, practical and effective. The research method refers to the analysis, design, development, implementation, and evaluation development model. The subjects of this research were class X students at Oikomene Manokwari High School, consisting of 24 students. Data collection procedures in the form of a questionnaire to determine validator and student responses to interactive e-modules as well as providing multiple choice questions to measure learning outcomes. Descriptive data analysis technique by calculating validation results and student learning outcomes. The research results showed that the media and material expert validation test results obtained a percentage of 96.67% with a very valid category. The results of the assessment of student responses in large group trials obtained an average percentage of 83.61% in the very practical category. The test results show that the average student learning outcome is 82.21 in the very high category. This research can be concluded that the flipbook-based interactive e-module on protist material meets the criteria of being valid, practical and effective in improving student learning outcomes.